Metaphysics from a Biological Point of View - Boulter, S. author. aut Link
VI, 179 p.
Keywords: Many philosophers in the analytic tradition are now convinced that metaphysical questions are worth pursuing, but we still lack a convincing meta-metaphysics and methodology. This essay offers an account of how we should conduct our business qua metaphysicians.